Development of Co/Co9S8 metallic nanowire anchored on N-doped CNTs through the pyrolysis of melamine for overall water splitting - Anchu Ashok (14152020) (2021)
Herein, we report the successful synthesis of Co9S8 metal-sulfide nanowire trapped in multi walled carbon nanotube (MWCNT), which was subsequently found to be an effective catalyst for water splitting. Melamine pyrolysis together with a Co precursor results in MWCNTs, with the addition of sulfur during synthesis enhancing the surface area, pore size, and oxygen vacancy defects in the nanotubes. The hierarchical structure of Co/Co9S8/CNT products boosted the electron mobility and mass transport for both the oxygen evolution (OER) and hydrogen evolution reaction (HER) in alkaline medium. Doping the catalyst surface with Pyridinic-N atoms, Graphitic-N atoms and thioamide S-atoms dramatically improved the bifunctional electrocatalytic performance by lowering the overpotentials for OER and HER reactions. The Co/Co9S8/CNT generated a current density of 10 mAcm−2 water-splitting current by applying a cell voltage of only 1.5 V. Further, Co/Co9S8/CNT showed excellent stability. The mechanism of Co8S9 nanowire formation in the MWCNT was also investigated. Other Information Published in: Electrochimica Acta License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.electacta.2020.137642